Head teachers’ conception of gifted students in mathematics in Swedish upper secondary school - Mattsson, Linda (NOMAD Nordic Studies in Mathematics Education, 2010)
The article presents a study of how Swedish upper secondary head teachers, working within mathematically intensive study programs, conceptualize giftedness in mathematics. The study is based on a survey of 34 randomly selected head teachers, in a population of about 400, who have answered questions about how they character- ize and detect gifted mathematics students. The results show that teachers characterize such students as creative, strong in logical ability and keen in their motivation for mathematics. The teachers detect such students by the students’ own initiative for engaging in mathematics, their inclination to orally reason about mathematics and their successfulness on tests. The findings, which are in accordance with results from internationally published studies, are of importance to the current discussion on special provision for gifted students in Sweden.